THE ORGANIZATION AND PROJECT MANAGEMENT OF DEVELOPMENT IN COMMERCIAL BANK - Роговая, Оксана Николаевна; Роговой, Антон Иванович (Eastern-European Journal of Enterprise Technologies, 2013)
In current economic situation and constantly become tougher competition in the financial services market one of the foreground criterion becomes proximity location of branch bank to potential customer. That is why the optimization works of the network of commercial banks and their branches appear often enough and therefore demand systematizing of all process. As opening of branches for small banks is not a regular activity, it is offered not to create separate branch for solving of such tasks but to use weak matrix organizational structure for integration of project management into current organizational structure. In this case the role of the project manager can carry out one of a top managers. In the article it is given network schedule of the real project as for opening of the territorial, insular branch of one of the commercial banks and also are presented the main stages of management of this project.